Characterization of Fly-ash using Electrochemical Impedance Spectroscopy. (2017) - Suryanto, Benny; McCarter, W. John; Starrs, Gerry; Chrisp, T. Malcolm
Abstract: Electrochemical impedance spectroscopy is used to obtain the electrical properties of fly-ash over the frequency range 100Hz-10 MHz. A range of presentation formalisms are exploited to characterize and assess this material in terms of its unburnt carbon content and pozzolanic reactivity. Fly-ash from a number of power stations within the UK, which differ in carbon content and fineness are used within the experimental programme. It is shown that the methodology could be exploited to index both the pozzolanicity and the presence of carbon in the ash. A number of additional features make this testing methodology of interest: the method is non-destructive and non-invasive; samples need not be restricted to cement pastes as mortars and concretes can also be studied.